Zespół obkurczania torebki przedniej soczewki po operacjach fakoemulsyfikacji zaćmy - Chomańska, Urszula; Kraśnicki, Paweł; Proniewska-Skrętek, Ewa; Mariak, Zofia (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Cataract facoemulsification with continuous anterior capsulorhexis and foldable intraocular lens implantation into the capsular bag has become basic, standard method in cataract surgery and curvilinear capsulorhexis is the most common technique for opening the anterior lens capsule. The opening, made during the operation, within several months of postoperative evolution gradually constricts and in extreme cases it may even close completely. That course of healing is not desirable because of evoking a noted impairment of vision. Decreasing in the anterior capsule opening is observed mostly in eyes with weakened lens zonules. It happens in high myopia, retinitis pigmentosa, diabetes mellitus, retinopathia diabetica, pseudoexfoliation syndrome, uveitis and people of well advanced age. Inspired by observation of a particular, quite drastic case of capsule contraction syndrome, we attempted to analyze the causes, pathogenesis, risk factors, clinical course, prevention and treatment of options for that syndrome.